11th European Hypoxia Symposium Training Centre of the German Federal Police, Kührointalm / Berchtesgaden (Germany), 26th–28th September 2025 - Küpper, Thomas (Health Promotion & Physical Activity, 2025)
The meeting continues a long tradition since some colleagues have organized the first one in 2002 in Slovenia. Hundreds of lectures followed and after a short break during the COVID-19 period the Czech team continued at Kladno and now it takes place again at the Training Centre od the German Federal Police near Berchtesgaden. As usual colleagues were invited to contribute to all aspects of hypoxia. In addition to mountain medicine, there is diving medicine, intensive care medicine, aviation medicine, working in extreme conditions, training, and many more. There was also a special invitation to young scientists and students to present their theses. The presented abstracts are listed in alphabetical order of the first author.